Discovery of (E)-4-styrylphenoxy-propanamide: A dual PPARα/γ partial agonist that regulates high-density lipoprotein-cholesterol levels, modulates adipogenesis, and improves glucose tolerance in diet-induced obese mice - Dutra, Luiz A. [UNESP]; Lacerda, Mariella G.; Destro Inácio, Maiara [UNESP]; Martins, Johnny W.L. [UNESP]; Lopes Silva, Ana C. [UNESP]; Bento da Silva, Patricia [UNESP]; Chorilli, Marlus [UNESP]; Amato, Angélica A.; Baviera, Amanda M. [UNESP]; Passarelli, Marisa; Guido, Rafael V.C.; Dos Santos, Jean L. [UNESP] (Elsevier, 2022)
Peroxisome proliferator-activated receptors are promising therapeutic targets for metabolic diseases, including obesity, diabetes, and dyslipidemia. This study describes the design, synthesis and pharmacological evaluation of stilbene-based compounds as dual PPARα/γ partial agonists with potency in the nanomolar range. In vitro and in vivo assays revealed that the lead compound (E)-4-styrylphenoxy-propanamide (5b) removed 14C-cholesterol from the foam cells through apolipoprotein A-I and High-Density Lipoprotein-2. In the high-fat diet-induced obesity mouse model, the oral administration of compound 5b increased HDL levels, paraoxonase-1 activity, and insulin sensitivity, and decreased glucose levels. Moreover, the adipogenesis pathway and triglyceride accumulation slightly changed in the adipocyte cells upon treatment with compound 5b, without affecting the body weight and adipose tissue in obese mice. Compound 5b did not affect the plasma levels of hepatic and renal injury biomarkers. Thus, stilbene-based compound 5b is a promising prototype for developing novel candidates to treat dyslipidemia and diabetes.
Keywords: Adipogenesis; Glucose homeostasis; HDL-C; PON1; PPARs; Stilbene